Kaidah Fiqhiyyah Yang Berkaitan Dengan Masalah ‘Iddah - NISA, KHAIRATUN; ADLY, MUHAMMAD AMAR; FIRMANSYAH, HERI (Albayan Journal of Islam and Muslim Societies, 2024)
The ‘iddah period in Islamic family law serves as an essential safeguard for lineage, the dignity of women, and post-marital social stability. Qaidah Fiqhiyyah provide a normative foundation that elucidates the wisdom and objectives underlying the establishment of ‘iddah. This study employs a qualitative method with a literature review approach. Data were collected from primary and secondary sources, including classical and contemporary fiqh literature as well as Indonesian Islamic legal regulations. Two qaidah fiqhiyyah related to the issue of ‘iddah are discussed in this study. These qaidahs have been interpreted by scholars from the four major Islamic schools of thought, reflecting diverse perspectives that ultimately converge on a shared objective: the protection of women's rights. The ‘iddah period is not merely a ritual obligation, but a legal mechanism that realizes the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly in preserving lineage and providing space for reflection and reconciliation. Understanding these principles is crucial for strengthening a just and compassionate Islamic family law system in the modern era.